Commercial Operator Liability in the New Space Era - Paul B. Larsen (AJIL Unbound, 2019)
Both national and international laws apply to collisions by space vehicles and objects in outer space and with the surface of the Earth. International treaties govern collisions involving commercial operators from different states, while domestic laws govern claims by nationals against national commercial operators. Commercial operators may find themselves as defendants or become plaintiffs when others cause them damage. This essay discusses liability in the new space era from the point of view of these operators, including both outer space and surface liabilities. It examines liability exposure, describes different regimes governing liability, and identifies prospective legal changes.